2003
DOI: 10.1002/adem.200390011
|View full text |Cite
|
Sign up to set email alerts
|

On the Behavior of Hot Crack Formation During Solidification in Fe–Ni Alloys

Abstract: High temperature tensile properties during solidification have been determined for two Fe±Ni alloys, in order to understand the hot cracking (tearing) mechanism. Tensile tests were made on ªin situº solidified samples. Hot cracking susceptibility was determined by using the transition temperature for area reduction (hot ductility), i.e. the transition temperature between a brittle and a ductile fracture. True strain and ultimate tensile stress were also measured. The results from the tensile tests were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Figure 5 shows that critical strain is increased from 1.9 to 2.5 % by decreasing the cool side temperature of the specimen from 1 250 to 950°C. Since the various cool side temperatures were obtained with the same cooling rate, which implies the supersaturation of vacancies 7) of each specimen was equal, the variation in critical strain can be related to the area where liquid coexists with solid. Lower temperature on the cool side results in a smaller area of solid/liquid co-exist region due to a higher temperature gradient.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 shows that critical strain is increased from 1.9 to 2.5 % by decreasing the cool side temperature of the specimen from 1 250 to 950°C. Since the various cool side temperatures were obtained with the same cooling rate, which implies the supersaturation of vacancies 7) of each specimen was equal, the variation in critical strain can be related to the area where liquid coexists with solid. Lower temperature on the cool side results in a smaller area of solid/liquid co-exist region due to a higher temperature gradient.…”
Section: Methodsmentioning
confidence: 99%
“…Kim, Hansson and Fredriksson have observed that an Invar alloy with a sulfur content of 14 ppm is more susceptible to hot cracking than an alloy with a sulfur content of 4 ppm. 15) They suggested that S atoms segregated to the boundaries could quantum mechanically weaken the boundaries and the work for crack nucleation decrease as a result of a reduction in the surface tension due to S segregation. Therefore, they suggested that hot cracking could occur even when liquid films are not present along the grain boundaries.…”
Section: Grain Growth Under Temperature Gradient Andmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to advise an experimental method to verify this assumption. In an earlier investigation 9,10 of peritectic steels , no difference was observed in the stress-strain behaviour between steels solidifying primarily austenite and steels solidifying to ferrite. In the present study, a new experimental method was developed in order to verify the above assumption.…”
Section: Introductionmentioning
confidence: 80%
“…It is often formed at a location of stress concentration associated with a sudden change in the transversal cross section or hot spots due to the obstructed contraction of the solidifying material. In recent years, many studies have been conducted to investigate the hot tearing susceptibility (HTS) and the underlying mechanisms of the different alloy systems, such as steel, Al alloys, and Mg alloys …”
Section: Introductionmentioning
confidence: 99%